2019
DOI: 10.1038/s41436-019-0525-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sequencing as a first-line methodology for cystic fibrosis carrier screening

Abstract: PurposeMedical society guidelines recommend offering genotyping-based cystic fibrosis (CF) carrier screening to pregnant women or women considering pregnancy. We assessed the performance of sequencing-based CF screening relative to genotyping, in terms of analytical validity, clinical validity, clinical impact, and clinical utility.MethodsAnalytical validity was assessed using orthogonal confirmation and reference samples. Clinical validity was evaluated using the CFTR2 database. Clinical impact was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…17 Our results show NGS-based CS is particularly advantageous for CF screening in East and South East Asians and African Americans because some of the most common variants in these groups are not included in the CF23 panel. 25,26 Likewise, our approach to SMA screening also allows for the identification of considerably more at-risk pregnancies, particularly among African Americans where identification of the g.27134T>G variant (linked to two copies of SMN1) facilitates identification of those at risk to be silent (2 + 0) carriers. We screened for disorders typically associated with AJ ancestry in non-AJ ethnicities, and for variants in genes with frequent disease occurrence but without standard panels, such as for DMD-related dystrophinopathies and hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our results show NGS-based CS is particularly advantageous for CF screening in East and South East Asians and African Americans because some of the most common variants in these groups are not included in the CF23 panel. 25,26 Likewise, our approach to SMA screening also allows for the identification of considerably more at-risk pregnancies, particularly among African Americans where identification of the g.27134T>G variant (linked to two copies of SMN1) facilitates identification of those at risk to be silent (2 + 0) carriers. We screened for disorders typically associated with AJ ancestry in non-AJ ethnicities, and for variants in genes with frequent disease occurrence but without standard panels, such as for DMD-related dystrophinopathies and hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…This is because heterozygous variants are technically more difficult to detect and analyze. A recent analytical validation of an NGS-based carrier screen for cystic fibrosis demonstrated that NGS enabled accurate detection of the causal variants, achieving high sensitivity and specificity compared to the established genetic screening methods (Beauchamp et al, 2019). According to the experience of the International Rare Diseases Research Consortium (IRDiRC), the utility of WES for rare disease gene identification is beyond any doubt (Boycott et al, 2017).…”
Section: Is It Time For Genome Testing To Be At the First Line Of Haementioning
confidence: 99%
“…These vary from using allele-specific testing such as genotyping arrays for a limited number of variants associated with a single AR disease gene (Picci et al 2010), to GWS to test all variants found in any number of AR genes (Punj et al 2018). A targeted approach simplifies variant interpretation and avoids variants of uncertain significance (VUS) but risks missing carriers if only a limited number of causative variants are genotyped (Stafler et al 2016;Beauchamp et al 2019a) and would require regular reviewing and updating. Additionally, there is wide variability between laboratories regarding which variants to report (Hoffman et al 2014), potentially resulting in substantial health disparities.…”
Section: Genes Versus Variantsmentioning
confidence: 99%